Stres Akademik Mahasiswa Aktif Angkatan 2018 dan 2019 Universitas Swasta di DKI Jakarta - Merry; Henny Christine Mamahit (Universitas Kanjuruhan Malang, 2020)
During their recovery journey, students face various academic problems that lead to stress. Academic stress is a depressed state experienced by students due to the mismatch between the desired state and academic demands. The purpose of this study was to describe the academic stress of active students in the 2018 and 2019 Classes. The population of this study were active students from universities in Jakarta for the 2018 and 2019 generations. The research sample was 106 respondents who were taken using accidental sampling technique. This research uses descriptive quantitative research method. The results of the descriptive analysis of academic stress variables were: 16% of respondents experienced academic stress in the high category, 46% in the high enough category, 31% in the low category, and 7% in the very low category.